Histological characteristics of rats` spleen in conditions of general dehydration. - O. O. Prykhodko (Морфологія, 2016)
Background. The study of morphological changes of immune organs in conditions of extreme factors still remains one of the most important in medicine due to daily influence of negative factors on the body. Dehydration is a stressful agent, often influencing human body in natural conditions and in the conditions of specific manufacture. Objective. To compare the changes of structural spleen components in conditions of experimental dehydration of rats of light and moderate degrees. Methods. The object of the study were 18 outbred white adult rats. 6 animals formed the control group. The group of experimental rats was in conditions of general dehydration by A.D.Soboleva: they were on a completely anhydrous diet. They were fed with granulated feed. In the first group (6 rats) we simulated mild dehydration, which was reached within three days. In the second group (6 rats) we simulated moderate degree of dehydration when water shortage was achieved within 6-7 days of the experiment. In order to study the structural components of the spleen histological sections were stained with hematoxylin-eosin, by the method of Van Gieson, and PAS-reaction was conducted. Results. Under the light microscopy rats` spleen of the control group has typical for rats structure. On the 3rd day of the experiment (mild dehydration) the conducted histological studies of the spleen showed, that medium-sized lymphoid follicles with well-distinguished T and B zones dominate in the white pulp. In some follicles the boundaries of reactive centers are expanded, there are strengthened macrophage and plasmocyte reactions. On the 6th day of the experiment (mild dehydration) medium follicles dominate in 2/3 of observations, more seldom - large. In large and medium-sized follicles we determine T- and B-zones. In 1/3 of observations we determine small follicles and almost no medium and large specimens. Small follicles are devastated, they are presented by T-lymphocytes, B-zones are not defined or expressed very poorly. There is increased plethora of the red pulp. The density of immune cells is moderate and focal accumulations of T -lymphocytes are not numerous. Conclusion. It was determined that within both terms of the experiment dehydration leads to similar morphological changes in the spleen. There is a slight hyperplasia of the white pulp in the spleen on the 3rd day of general dehydration. On the 6th day in the majority of the observations we determined signs of severe hyperplasia of the white pulp. At the same time, a small number of observations in the white pulp show small follicles, presented only by T-lymphocytes. This shows the signs of a gradual depletion of splenic white pulp with general dehydration of average degree.